HUMAN SACRIFICE AND PROPAGANDA IN POPULAR MEDIA: MORE THAN MORBID CURIOSITY - Tatlock, Jason (Dialogue, 6(1), 2019)
Representations of human sacrifice, whether based upon real or fictitious events, powerfully demonstrate societal norms and fascinations related to the acceptability of slaying humans for religious or national interests, particularly given the divisive and bloody nature of the topic. Readers of eye-witness accounts, newspaper reports, and historical narratives, and viewers of cinematic productions, war posters, and political cartoons come face to face with the beliefs and agendas of the creators of popular media. Such sources represent the slaying of victims in sacred rituals, as individuals attempt to demarcate societal boundaries along the etic/emic spectrum, be they commentaries on their own cultures or on contemporary foreigners. Those who write about or portray human sacrifice have, in several instances, done so with propagandistic aims related to ethnocentrism, imperialism, and a perceived religious superiority that transfer the topic beyond the realm of mere morbid curiosity to justify forms of dominance like territorial conquest, militarism, and slavery. Moving from the ancient world to contemporary cinema, this study demonstrates both the antiquity of such propagandistic goals and their relevancy to recent portrayals of human sacrifice in film. While Apocalypto (2007) and The Wicker Man (1973) align closely with the historical examples presented, especially in relation to the issue of a perceived Christian ascendancy, The Purge (2013) largely diverges from them. The Purge counters a dominant American ideal that sacrifice for the state is valuable and accentuates the need to protect ethnic minorities from oppression. Keywords: human sacrifice, ethnocentrism, imperialism, religious superiority, propaganda, sati, India, West Africa, Rome, Meso-America, United States, Apocalypto, The Wicker Man, and The Purge
Keywords: Type of access: Open Access